Research for controlling the hybrid renewable energy connected to the low voltage grid - Trương Đình Nhơn; Ngô Văn Thuyên; Nguyễn Thị Mi Sa; Hoàng An Quốc (Journal of Technical Education Science, 2021)
In this paper, the authors present the responsive control and stability of the integrated power generation system including wind power and solar power when operating in grid-connected mode to determine the most efficient and stable working mode for the system. An integrated renewable energy sources supplying power to the load for 24 hours is proposed in this study. Simulation results in the time-domain are performed on the Simulink tool of Matlab software. Simulation results in grid-connected mode with the changing of load and input conditions such as solar radiation and wind speed occurring during operation are also considered. From the simulation results, it can be concluded that the proposed Droop controller in the the proposed integrated power generation system will support the system operate better and more stable, helping to save power consumption from the grid.